Applications of Surface-Enhanced Raman Scattering in Biochemical and Medical Analysis - Szaniawska, Aleksandra; Kudelski, Andrzej (Frontiers in Chemistry, 2021)
In this mini-review we briefly describe certain recently developed applications of surface enhanced Raman spectroscopy (SERS) for determining various biochemically (especially medically) important species, from ones as simple as hydrogen cations to those as complex as specific DNA fragments. We present a SERS analysis of species whose characterization is important to our understanding various mechanisms in the human body, and show its potential as an alternative for methods routinely used in diagnostics and in clinics. Further, we explain how such SERS-based sensors operate, and point out future prospects in this field.